Molecular insights into the mechanisms of drug-induced resistance reversion in Staphylococcus aureus, Escherichia coli and Acinetobacter baumannii - Reva, Oleg N. (University of Pretoria, 2020)
Dissertation (MSc Biochemistry (Bioinformatics))--University of Pretoria, 2020.